ANALISIS KONDISI DAN KEBUTUHAN PERALATAN PRAKTEK KONSTRUKSI PROGRAM KEAHLIAN TEKNIK BANGUNAN SMKN 5 PADANG - 735-744 , Lathi Fathul Akhfa (CIVED, 2015)
ABSTRACT This descriptive research aimed to determine the condition and needs of the equipment for construction practice learning in Building Engineering Program at SMK Negeri5 Padang in the academic year 2014/2015. The object of this research was the equipment of masonry construction practice that were available at the Building Workshop of SMK Negeri5 Padang in year 2015. The samples were all learning equipment for masonry construction practice that were available at the Building Workshop of SMK Negeri5 Padang. Research was done by conducting observation and interviews. To determine the equipment needs, a descriptive analysis was done. Based on the results of data analysis, the research conclusionsareas follows: (1) The condition of the masonry construction practice equipment arepretty good and workable to be used in practice, but there are a few tools that need to be added. (2) The equipment required are as follows: cutting saws, splitting saws, hammers, mortar trowels, water pass, buckets, square, line bobbins and wheelbarrows. The equipment that have not yet meet the required amount are: measuring tapes, hoes, yarns, shovels, water hoses, plumb-bobs, mortar boxes, and plaster trowels. Keywords: analisis kondisi, analisis kebutuhan, peralatan